ANALISIS FAKTOR-FAKTOR KEMISKINAN KABUPATEN DI SUMATERA - Yunita Ariani Zebua; Fajar Restuhadi; Syaiful Hadi (Berkala Perikanan Terubuk, 2017)
Poverty is one Fundamental issues serious concern which become from the government.  An important aspect of supporting poverty tackling strategies is the provision of accurate and targeted poverty data. BPS presents data set and poverty information (data mining) and indicators related to poverty issues in level regency/city and province.   The island of Sumatra is the region with the densest population after  Java with the distribution of poverty of 21.6%. The purpose of this research was to analyze the poverty factors of regencies/cities  in Sumatera. The research consist of 6.468 cell data covering 154 regencies/cities in Sumatera and 42 poverty indicators which are processed with factor analysis. The research results showed that the factors of poverty of the Regency and City in Sumatera are: 1) economic factors, employment and housing facilities, 2) under-five health factors,  3)  factors  of  labor  and  clean  water  facilities,  4)  social  factors  and assistance of raskin, 5 ) Maternal health factors, education and government facilities.There fore, the government shoul dpayattentito the ways of poverty alleviation by looking at various factors that exist in each region.